A Review of the Efficacy of Nanomaterial-Based Natural Photosensitizers to Overcome Multidrug Resistance in Cancer - Jagadeesh Rajaram; Lokesh Kumar Mende; Yaswanth Kuthati (MDPI AG, 2024)
Natural photosensitizers (PS) are compounds derived from nature, with photodynamic properties. Natural PSs have a similar action to that of commercial PSs, where cancer cell death occurs by necrosis, apoptosis, and autophagy through ROS generation. Natural PSs have garnered great interest over the last few decades because of their high biocompatibility and good photoactivity. Specific wavelengths could cause phytochemicals to produce harmful ROS for photodynamic therapy (PDT). However, natural PSs have some shortcomings, such as reduced solubility and lower uptake, making them less appropriate for PDT. Nanotechnology offers an opportunity to develop suitable carriers for various natural PSs for PDT applications. Various nanoparticles have been developed to improve the outcome with enhanced solubility, optical adsorption, and tumor targeting. Multidrug resistance (MDR) is a phenomenon in which tumor cells develop resistance to a wide range of structurally and functionally unrelated drugs. Over the last decade, several researchers have extensively studied the effect of natural PS-based photodynamic treatment (PDT) on MDR cells. Though the outcomes of clinical trials for natural PSs were inconclusive, significant advancement is still required before PSs can be used as a PDT agent for treating MDR tumors. This review addresses the increasing literature on MDR tumor progression and the efficacy of PDT, emphasizing the importance of developing new nano-based natural PSs in the fight against MDR that have the required features for an MDR tumor photosensitizing regimen.